HUBUNGAN PEMAKAIAN DOT DENGAN FREKUENSI KEJADIAN DIARE PADA BALITAÂ DI DESA PEKUWON Â BANGSAL MOJOKERTO - Zakiyah, Ana; Windartik, Emyk (Jurnal Keperawatan Bina Sehat, 2014)
ABSTRACTThe occurrence of diarrhea in toddlers is from the factors that cause behavior spread germs mainly enteric-related interaction behavior of mothers in parenting and environmental factors where the children live. Behavioral factors that caused the spread of enteric disease and increases the risk of the occurrence of diarrhea that does not provide exclusive breast milk in full in the first month of life, provide infant formula in baby bottles. The purpose of this research is to know the relation of the use dot with frequency occurrence of diarrhea in toddlers ages 1-3 years. Design of this research is analytic korelasional with cross sectional approach. The variable of this research are use dot as the independent variable and frequency of diarrhea as the dependent variable. The population of this research aremothers with children ages 1-3 years in Pekuwon village Bangsal Mojokerto as much as 139 respondents. Samples taken with the simple random sampling technique as much as 101 respondents. The results showed the existence of a relationship between the use of dot with the occurrence of diarrhea in toddlers ages 1-3 years in the village Pekuwon Bangsal Mojokerto. The use of dot does not clean and sterile would be the place-breeding germs so that if these are used then the dot will experience diarrhea with a frequency that is increasingly frequent. So expect health workers provide counseling about diarrhea at the time of posyandu so mom can better understand and understand about diarrhea in toddlers.Keywords: Baby bottle, diarrhea, toddlers